If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + -1(5m + 8) = 5 + 4m + -13 Reorder the terms: 18 + -1(8 + 5m) = 5 + 4m + -13 18 + (8 * -1 + 5m * -1) = 5 + 4m + -13 18 + (-8 + -5m) = 5 + 4m + -13 Combine like terms: 18 + -8 = 10 10 + -5m = 5 + 4m + -13 Reorder the terms: 10 + -5m = 5 + -13 + 4m Combine like terms: 5 + -13 = -8 10 + -5m = -8 + 4m Solving 10 + -5m = -8 + 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. 10 + -5m + -4m = -8 + 4m + -4m Combine like terms: -5m + -4m = -9m 10 + -9m = -8 + 4m + -4m Combine like terms: 4m + -4m = 0 10 + -9m = -8 + 0 10 + -9m = -8 Add '-10' to each side of the equation. 10 + -10 + -9m = -8 + -10 Combine like terms: 10 + -10 = 0 0 + -9m = -8 + -10 -9m = -8 + -10 Combine like terms: -8 + -10 = -18 -9m = -18 Divide each side by '-9'. m = 2 Simplifying m = 2
| 3x-5=7x+2-3 | | (4x-5)+(2x+20)=45 | | 6x+x-0.9=6x+0.9 | | -3-6X=28 | | X+65X+1000=0 | | (18)-2y-4= | | 3/4x+2-5/4=-6 | | 13=2f-5 | | 6x+3-8x-16=0 | | 5x+7=-7x+43 | | 9t=4 | | -2(3x+1)-10=4 | | 5x+3=33-x | | 1/4x+4=-6 | | 2-x=-2x-12 | | 3x+5=-x+13 | | 3[4-2(x-1)]=3x+3 | | 5x+6=2x+27 | | -2/7y+3/7=2/5y+4/5 | | 18x-9=18x-9 | | 7y-4-4y-1= | | -7x+2=7x+156 | | 2+3x=5x+20 | | -x+9=-9 | | 1+4x=3x-10 | | 3ab^2*4a^2b^4=0 | | 1-6x=6x+133 | | 0=4x^2-1600x+174000 | | r^4-7r^2+6r=0 | | 3.6-3=2.6x | | -15x^2-11=0 | | 1x-8=-20+2x |